La colaboración en I+D en la industria auxiliar del automóvil en Catalu\~na. Análisis según el tama\~no empresarial - Francisco Llorente Galera (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– This article discusses theoretically why companies cooperate in carrying out their R&D, and doing so with several external agents. From a sample of original equipment manufacturers suppliers (OEMS) located in Catalonia, we checked if they incorporated products innovation, research, design, product development phases, and if they collaborated with external agents in doing their R&D, differentiated by property capital (domestic versus foreign) and company size. It was shown that large companies are those who performed R&D in greater proportion, however, and the smaller ones the least. A very small number of firms cooperate with the external agents considered, and they are all large companies.
Keywords: L62; O32; M19; 650; research and development; suppliers; automotive; cooperation; Catalonia